Efektivitas Intervensi Edukasi Nutrisi pada Ostomate Paska Operasi Digestif - Ria Andjarwati; Dewi Gayatri; Yati Afiyanti (Journal of Telenursing (JOTING), 2022)
This study aims to investigate and describe the types and formats of nutrition education interventions in colon cancer patients with a postoperative stoma and to examine the effect of nutrition education interventions on ostomate nutritional status. The method used is a systematic review through article searches on the Google Scholar, ScienceDirect and Proquest databases. The results showed that there was a significant improvement in the nutritional status of the patients. The ostomates can maintain fluid and electrolyte balance and albumin levels in the blood while suppressing the incidence of sepsis. One article showed a decrease in ostomate re-admission due to malnutrition (10.3%). In conclusion, the effectiveness of nutrition education intervention can improve the nutritional status of colorectal cancer patients with a stoma. Keywords: Diet Education, Nutrition Education, Ileostomy, Colostomy, Ostomate, Ostomy, Postoperative Follow-up